PENYERAPAN HUKUM ISLAM PADA KOMUNITAS ADAT (STUDI ANTROPOLOGI HUKUM DI BADUY, KAMPUNG NAGA DAN MARUNDA PULO) - Abdurrahman Misno (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
The first community to accept Islam was the tenant at the coastal areas of Sumatra,Java, Sulawesi, Kalimantan, Maluku and Nusa Tenggara. After that Islam disseminated to rural areas throughout the country as the consequence of their reception of Islamic law. However, the fact was not all Islamic law accepted and implemented, because they already have customs practiced continuously by hereditary generations long before the arrival of Islam. Some custom in Indonesia, which still survive was practiced by indigenous community such as Baduy, Kampung Naga and Marunda Pulo. Research shows that the reception of Islamic law by the community of Baduy in the implementation of Islamic law marriage that is reading the creed of the Prophet Muhammad Pbuh, the presence of dowry and marriage records by KUA, especially on the community of Outer Baduy. Meanwhile the community of Inner Baduy has not been accept the Islamic law a lot in the field of marriage. Reception in the field of inheritance was limited to the mention of the terms in Islamic inheritance, while the division still follow their customs that divide the estate equally both boys and girls. While the community of Kampung Naga reception occurs in the majority of law and worship in particular muamalah espescially in wedding. At issue still retain their inheritance patterns of inheritance according to their customs that divide the inheritance with equal parts between boys and girls. Kampung Marunda Pulo reception of Islamic law in worship and muamalah. Islamic law reception process occurs due to internal factors (custom character and creed) and external (social interaction and the power of the state). Keywords: Reception of Law, Indigenous Community, Adat, Baduy, KampungNaga, Marunda Pulo and Theory Reception through Selection-modification.